Effects of Lactobacillus plantarum and Pediococcus acidilactici co-fermented feed on growth performance and gut microbiota of nursery pigs - Yang, Yuzeng; Yan, Guohua; Meng, Xianhua; Wang, Xu; Zhao, Zhiqiang; Zhou, Shuguang; Li, Guangdong; Zhang, Qiuliang; Wei, Xiaoyuan (Frontiers in Veterinary Science, 2022)
Fermented feed has been used extensively as a growth promoter in agricultural animal production. However, the effects of fermented feed on swine gut microbiota are still largely unknown. The work presented here aimed to investigate the growth performance and gut microbiota of nursery pigs receiving LPF diet (10% Lactobacillus plantarum and Pediococcus acidilactici co-fermented feed + basal diet) compared with pigs receiving NC diet (basal diet). The data showed LPF diet numerically improved average daily gain and significantly increased fecal acetate, butyrate, and total SCFA concentrations. Furthermore, gut microbiota structure and membership significantly changed in response to the addition of fermented feed in diet. Gut microbiota results indicated that LPF treatment significantly enriched SCFA-producing bacteria such as Megasphaera, Roseburia, Faecalibacterium, Blautia, Selenomonas, Dialister, Acidaminococcus, Ruminococcus, and Bifidobacterium. Some of these bacteria also had anti-inflammatory functions. Overall, these findings suggested that Lactobacillus plantarum and Pediococcus acidilactici co-fermented feed benefited growth performance and established potential health impacts on gut microbiota of nursery pigs.